The Effect of Sanitation Hygiene Information Quality on Digital Maps on Visit Intention to Tourism Villages: An Extended Technology Acceptance Model - Isnein Akbar; Abdulah Muzakar (Sumber Belajar Sejahtera, 2026)
Sanitation and hygiene are essential components of sustainable tourism, yet their role as publicly consumed information on digital platforms has received limited scholarly attention. This study examines how the quality of sanitation hygiene information on digital maps influences visit intention to tourism villages through perceived usefulness and information trust, drawing on an extended Technology Acceptance Model. Using survey data from 150 digital map users, the findings indicate that sanitation hygiene information quality positively affects perceived usefulness and trust, which in turn significantly increase visit intention. These results suggest that improving the visibility, accuracy, and credibility of sanitation hygiene information on digital maps represents a cost-effective strategy to support sustainable tourism governance and destination competitiveness.